2019
DOI: 10.1167/19.11.4
|View full text |Cite
|
Sign up to set email alerts
|

How exogenous spatial attention affects visual representation

Abstract: Orienting covert spatial attention to a target location enhances visual sensitivity and benefits performance in many visual tasks. How these attention-related improvements in performance affect the underlying visual representation of low-level visual features is not fully understood. Here we focus on characterizing how exogenous spatial attention affects the feature representations of orientation and spatial frequency. We asked observers to detect a vertical grating embedded in noise and performed psychophysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 71 publications
3
20
0
Order By: Relevance
“…These novel findings advance our understanding of the effects of exogenous and endogenous attention on a fundamental measure of visual function, contrast sensitivity. Although many previous studies have demonstrated that both exogenous attention ( Barbot et al, 2011 ; Barbot et al, 2012 ; Cameron et al, 2002 ; Carrasco et al, 2000 ; Carrasco & McElree, 2001 ; Fernández et al, 2019 ; Foley & Schwarz, 1998 ; Herrmann et al, 2010 ; Ling & Carrasco, 2006b ; Liu et al, 2005 ; Morgan et al, 1998 ; Pestilli et al, 2007 ; Pestilli & Carrasco, 2005 ; Smith et al, 2004 ; Solomon, Lavie, & Morgan, 2004 ) and endogenous attention ( Barbot et al, 2012 ; Dosher & Lu, 2000a , 2000b ; Herrmann et al, 2010 ; Huang & Dobkins, 2005 ; Lee et al, 1997 , 1999 ; Ling & Carrasco, 2006a , 2006b ; Lu et al, 2002 ; Lu & Dosher, 1998 , 2000 , 2004 ; Morrone et al, 2002 , 2004 ) improve contrast sensitivity, we characterized their effects across SF and eccentricity to reveal that each operates differently relative to the constraints of the visual system at each eccentricity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These novel findings advance our understanding of the effects of exogenous and endogenous attention on a fundamental measure of visual function, contrast sensitivity. Although many previous studies have demonstrated that both exogenous attention ( Barbot et al, 2011 ; Barbot et al, 2012 ; Cameron et al, 2002 ; Carrasco et al, 2000 ; Carrasco & McElree, 2001 ; Fernández et al, 2019 ; Foley & Schwarz, 1998 ; Herrmann et al, 2010 ; Ling & Carrasco, 2006b ; Liu et al, 2005 ; Morgan et al, 1998 ; Pestilli et al, 2007 ; Pestilli & Carrasco, 2005 ; Smith et al, 2004 ; Solomon, Lavie, & Morgan, 2004 ) and endogenous attention ( Barbot et al, 2012 ; Dosher & Lu, 2000a , 2000b ; Herrmann et al, 2010 ; Huang & Dobkins, 2005 ; Lee et al, 1997 , 1999 ; Ling & Carrasco, 2006a , 2006b ; Lu et al, 2002 ; Lu & Dosher, 1998 , 2000 , 2004 ; Morrone et al, 2002 , 2004 ) improve contrast sensitivity, we characterized their effects across SF and eccentricity to reveal that each operates differently relative to the constraints of the visual system at each eccentricity.…”
Section: Discussionmentioning
confidence: 98%
“…The current findings also provide possible explanations for discrepant findings in the literature regarding the effects of exogenous attention on contrast sensitivity across SF. A recent study (Fernández et al, 2019) used psychophysical reverse correlation to assess how exogenous attention altered sensitivity to orientation and SF to improve task performance. The authors found that behavioral improvements were not associated with enhanced sensitivity to SFs, which would seemingly conflict with the enhancements observed here.…”
Section: Exogenous and Endogenous Attention Distinctively Alter The Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown perceptual benefits at locations that have been previously cued, even when no eye movement is made, confirming that it is possible to orient attention covertly (Posner 1980; see: Posner 2015 for a review). These studies have mostly used simple detection responses, but covert orienting can also improve the discimination of spatial frequency and lower the contrast threshold for orientation discimination (Barbot et al 2012; Cameron et al 2002; Carrasco 2011; Fernández et al 2019; Lee et al 1999; Pestilli and Carrasco 2005; Solomon 2004). Given the strong similarities between the overt and covert process, we ask whether the phenomenon of saccadic inhibition, which arises with striking regularity in overt responses, extends to covert orienting behaviour.…”
Section: Introductionmentioning
confidence: 99%